1986
DOI: 10.2135/cropsci1986.0011183x002600010033x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Early Season Square Removal on Three Leaf Types of Cotton1

Abstract: In certain environments, reduced leaf‐open canopy cottons (Gossypium hirsutum L.) allow more light penetration and air circulation within their canopies than do normal leaf types. However, too much reduction in canopy can reduce overall productivity and economic yield. Removal of floral buds (squares) early in the season has been shown to result in larger plant size. Square removal was carried out in the field (fine‐silty, mixed, thermic, Aquic Fragiudalf soil type) on normal, okra, and super okra leaf type ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
4

Year Published

1988
1988
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 0 publications
4
19
0
4
Order By: Relevance
“…Moderate increases in biological yield (7.1%) and seed cotton yield (8.6%) were obtained under field conditions, although no yield advantage was found for potted plants. These results are in agreement with previous findings in which early reproductive sink removal increased the vegetative growth and favored more productive fruiting from later-developed positions to compensate for earlier losses (Kletter and Wallach 1982;Kennedy et al 1986;Ungar et al 1987;Jones et al 1996;Sadras 1996;Bednarz and Roberts 2001). Most importantly, the removal of early fruiting branches delayed the main-stem leaf senescence characterized by increase of chlorophyll concentration and photosynthetic activity of leaves.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moderate increases in biological yield (7.1%) and seed cotton yield (8.6%) were obtained under field conditions, although no yield advantage was found for potted plants. These results are in agreement with previous findings in which early reproductive sink removal increased the vegetative growth and favored more productive fruiting from later-developed positions to compensate for earlier losses (Kletter and Wallach 1982;Kennedy et al 1986;Ungar et al 1987;Jones et al 1996;Sadras 1996;Bednarz and Roberts 2001). Most importantly, the removal of early fruiting branches delayed the main-stem leaf senescence characterized by increase of chlorophyll concentration and photosynthetic activity of leaves.…”
Section: Discussionsupporting
confidence: 93%
“…Compensation for early fruit removal in cotton has been of great interest to both agronomists and entomologists, as it will not only help in establishing the recovery potential, but also provide a good experimental condition to study association between source and sink, as well as vegetative and reproductive growth (Dong et al 2008b;Zhang et al 2008). Numerous fruit removal studies have shown that reproductive sink removal enhances vegetative growth and development (Patterson et al 1978;Kennedy et al 1986;Ungar et al 1987;Jones et al 1996). Loss of early fruiting forms has also been shown to increase root growth (Sadras 1996;Dumka et al 2004), alter spatial yield distribution (Bednarz and Roberts 2001), and improve Cry1AC expression of transgenic Bacillus thuringiensis Berliner (Bt) cotton (Zhang et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This might be caused by cumulative effects of removal of squares. The results confirm the findings of Kennedy et al (1986). Also, it is indicated that flowering rate was increased by other flower removals and increase was apparently observed throughout two weeks later when removals were ended.…”
Section: Flowering Patternsupporting
confidence: 89%
“…Therefore, mid-season fruit loss may be less likely to be replaced. To fully compensate from mid-season square loss with minimum delay requires that more bolls on higher and more distal positions develop simultaneously after damage (Kennedy et al 1986, Jones et al 1996b, Bednarz and Roberts 2001. Our study showed a lower yield ranking for mid-season than early season fruit injury, indicating that some of the squares removed were not replaced.…”
Section: Discussionmentioning
confidence: 68%